The Effects of Microplastic Pollution on Marine Organisms and its Impact on Human Health: A Review - Aran Akbari; Jalil Jaafari (Caspian Journal of Health Research)
Microplastics (MPs) generally refer to plastic particles less than 5 mm in size. These pollutants are currently present in almost all marine environments and, due to their small size, are easily accessible to a wide range of marine organisms and are ultimately transported along the food web. The increasing presence of MP particles in the marine food chain has raised global concerns. MPs were first discovered in the guts of seabirds and have since been found in increasing concentrations. Exposure of marine organisms to MPs can lead to weight loss, reduced growth, reduced reproduction, changes in feeding behavior, changes in enzyme activity, initiation of stress response, and inflammatory response. MPs in marine environments provide a highly selective and flexible support platform for a variety of microbial communities, especially resistant pathogens. The accumulation of MPs in marine organisms consumed as human food has dangerous consequences for human health, leading to physical and chemical toxic effects. This study examines the effects of MPs and related contaminants on some of the most important marine organisms (plankton, bivalves, corals, fish, seabirds, and marine mammals) and also assesses the risks of human exposure to MPs through edible marine organisms.